A possible Chandra and Hubble Space Telescope detection of extragalactic WHIM towards PG 1116+215 - Bonamente M; Nevalainen J; Tilton E; Liivamagi J; Tempel E; Heinamaki P; Fang T (OXFORD UNIV PRESS, 2022)
We have analysed Chandra low energy transmission grating and XMM-Newton Reflection Grating Spectrometer (RGS) spectra towards the z = 0.177 quasar PG 1116+215, a sightline that is rendered particularly interesting by the Hubble Space Telescope (HST) detection of several OVI and HI broad Lyman alpha absorption (BLA) lines that may be associated with the warm-hot intergalactic medium (WHIM). We performed a search for resonance K alpha absorption lines from OVII and OVIII at the redshifts of the detected far-ultraviolet lines. We detected an absorption line in the Chandra spectra at the 5.2 sigma confidence level at wavelengths corresponding to OVIII K alpha at z = 0.0911 +/- 0.0004 +/- 0.0005 (statistical followed by systematic error). This redshift is within 3 sigma of that of an HI broad Lyman alpha of b similar or equal to 130 km s(-1) (corresponding to a temperature of log T(K) similar or equal to 6.1) at z = 0.092 79 +/- 0.000 05. We have also analysed the available XMM-Newton RGS data towards PG 1116+215. Unfortunately, the XMM-Newton data are not suitable to investigate this line because of instrumental features at the wavelengths of interest. At the same redshift, the Chandra and XMM-Newton spectra have OVII K alpha absorption-line features of significance 1.5 sigma and 1.8 sigma, respectively. We also analysed the available Sloan Digital Sky Survey (SDSS) spectroscopic galaxy survey data towards PG 1116+215 in the redshift range of interest. We found evidence for a galaxy filament that intersect the PG 1116+215 sightline and additional galaxy structures that may host WHIM. The HI BLA and the OVIII K alpha absorbers are within a few Mpc of the filament (assuming that redshifts track Hubble flow distances) or consistent with gas accreting on to the filament from either direction relative to the sightline with velocities of a few x 100 km s(-1). The combination of HST, Chandra, XMM-Newton and SDSS data indicates that we have likely detected a multi-temperature WHIM at z similar or equal to 0.091-0.093 towards PG 1116+215. The OVIII Ka absorption line indicates gas at high temperature, log T(K) >= 6.4, with a total column density of the order of log N-H(cm(2)) >= 20 and a baryon overdensity delta(b) similar to 100-1000 for sightline lengths of L = 1-10 Mpc. This detection highlights the importance of BLA absorption lines as possible signposts of high-temperature WHIM filaments.